Stochastic cloaking: Concealing a region from diffusive particles - Connor Roberts; Ziluo Zhang; Helder Rojas; Stefano Bo; Carlos Escudero; Sébastien Guenneau; Gunnar Pruessner (Physical Review Research)
We introduce “stochastic cloaking,” where a region of space is concealed from an ensemble of diffusing particles whose individual trajectories are governed by a stochastic (Langevin) equation. Our simulations reveal how different interpretations of the Langevin equation affect the cloaking performance of an annular single-layer invisibility cloak of smoothly varying diffusivity in two dimensions. Near-perfect cloaking is achieved under the Itô convention, indicated by the cloak preventing particles from accessing an inner core without disturbing the particle density outside the cloak. The cloak's performance can be further improved by regularizing its singular behavior. We believe our demonstration of stochastic cloaking is a significant milestone, comparable to earlier developments that extended cloaking from optics and acoustics to thermodynamics.